Size, Growth Rates, and Merger Valuation. - Ramanathan, K. V.; Rappaport, Alfred (The Accounting Review, 1971)
This article aims to examine how relative differences in key financial variables among buyers and sellers affect the valuation of aggregate and hence the benefits arising from the merger to buyer's and seller's stockholders as well as the implications for merger strategy which buyer and seller might adopt. It also aims to carry out the foregoing analyses as of the time the merger transaction takes place and also over a specified planning horizon. A major conclusion of this article is that when two firms, experiencing unequal growth rates, merge on the basis of an exchange of shares, their combined value in the market will be less than the sum of the market values of the individual companies, as a result of a bias in the valuation models commonly used in security analysis. The specific source of this bias is the underestimate of the growth rate in combined earnings that results from typical forecasting methods. Another major conclusion is that although there is a valuation loss in total, the stockholders of the firm with the smaller of the two growth rates can experience valuation gains over a period of time at the expense of the other firm's stockholders. It would follow from this that a firm will always find it to the advantage of its stockholders to acquire or merge with firms experiencing higher growth rates than its own, provided these stockholders are willing to hold their stocks for a period of time, the minimum length of which would depend upon the relative sizes and growth rates of the merging firms.